Integrasi Transportasi Laut dalam Global Supply Chain: Kajian Literatur Mengenai Efisiensi, Keberlanjutan, dan Daya Saing - Falmawanty Patampang; Eliyanti A. Mokodompit (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to review the literature concerning the role of maritime transport across three principal dimensions: efficiency, sustainability and global competitiveness. The review is expected to provide a comprehensive and multi-faceted understanding of the contributions and challenges facing the maritime transport sector within the global logistics system. This research employs a qualitative descriptive approach (literature review). This methodology is deemed ideal as it allows the study to systematically and objectively collect, analyze, and synthesize findings from a diverse range of publications. The literature was categorized based on the three core components: efficiency, sustainability, and competitiveness. The review utilizes various secondary sources, including academic journals, scientific articles, and other relevant research. The study demonstrates that maritime transport plays a vital role in integrating, ensuring the smooth flow, and guaranteeing the efficiency of the Global Supply Chain (GSC). Two key findings emerge from this analysis: operational efficiency and the sustainability aspect. Operational efficiency is significantly driven by the adoption of digitalization and automation, which are crucial for effectively reducing global logistics costs. Meanwhile, sustainability has transformed from mere regulatory compliance into a fundamental prerequisite for competitive advantage within the maritime sector.